(untitled) (Medico Legal Update, 2020)
Cardiac laceration in child abuse cases is uncommon. Very few case studies are available illustrating the left ventricular rupture following blunt chest injuries. This article presents a case of sudden death of a two and a half year-old female child brought with history of fall on level ground while playing. The autopsy revealed multiple types of injuries over the whole body with duration varying from less than a day to more than 6 months old. Left ventricular rupture and liver laceration were the primary injuries contributing to death. Child abuse cases should never be examined with a preconception of finding the classical features of intracranial hematomas.